Design and technical realization of network-based management information system for modern agricultural demonstration areas - ZHU Guo-qun; WANG Ke; SHI Zhou (浙江大学学报. 农业与生命科学版)
Modern agricultural demonstration areas presently are key fields of agriculture construction in China. Almost all the jobs in the fields were limited to project construct and more attention in most of these areas was paid to new cultivar together with demonstration and extension of new technique, but with lag in informatization of management and network technique. In a case of modern agricultural demonstration areas in Shaoxing, a management information system of modern agricultural demonstration areas (MADAMIS) were built with the support of Geodatabase and the WebGIS technique. The established MADAMIS brought into being what we expected, including information query, information issuing, consultation and decision-making, map publication, multimedia teaching etc. It provides a new platform for network-based management, technique demonstration, consultation and decision-making of agriculture.